2020
DOI: 10.4240/wjgs.v12.i6.277
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the fat-dissociation method for nodal harvesting in gastric cancer

Abstract: BACKGROUND There is an increased need for accurate staging for gastric cancer treatment. Consequently, it is necessary to carefully examine all dissected lymph nodes for precise staging. Recently, the fat-dissociation method has been developed as a quick and accurate method for harvesting dissected lymph nodes of colorectal cancer cases. AIM To investigate the usefulness of the fat-dissociation method for harvesting dissected lymph nodes of gastric cancer cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In addition, our fat-dissociation solution at low concentration was commercialized as Imofully (Sysmex, Kobe, Japan). Similar to our study, it was reported that the results were excellent in short-term results such as the number of lymph nodes and the search time by using Imofully (Sysmex) 24,25 . It has been reported recently that molecular characterization of cancer based on gene expression is important for proper disease stratification 26 , and the appropriate drug treatment is selected according to specific mutations 2,9 .…”
Section: Discussionsupporting
confidence: 90%
“…In addition, our fat-dissociation solution at low concentration was commercialized as Imofully (Sysmex, Kobe, Japan). Similar to our study, it was reported that the results were excellent in short-term results such as the number of lymph nodes and the search time by using Imofully (Sysmex) 24,25 . It has been reported recently that molecular characterization of cancer based on gene expression is important for proper disease stratification 26 , and the appropriate drug treatment is selected according to specific mutations 2,9 .…”
Section: Discussionsupporting
confidence: 90%
“…In clinical practice, more than 15 lymph nodes are often targeted for harvesting (118). However, the actual number of affected lymph nodes is higher, and previous studies have reported that the number of lymph nodes harvested after D2 distal gastrectomy can exceed 40 (113,119,120). Many reports have suggested that a greater number of harvested lymph nodes is associated with better prognosis (121)(122)(123).…”
Section: Challenges In the Pathological Investigation Of Lymph Node Metastasis In Gastric Cancermentioning
confidence: 99%
“…Gastric cancer has many regional lymph nodes, many of which are small, and metastases can occur even in these small lymph nodes (61,62), which makes harvesting the nodes difficult. However, until now, the accuracy of node harvesting has been neglected (113,114). Worldwide, harvested nodes are likely to be handled by pathologists.…”
Section: Challenges In the Pathological Investigation Of Lymph Node Metastasis In Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In some non-specialized Western centers, it is generally achieved from formalin-fixed (FF) samples by pathologist during the grossing procedure; although this method is time-consuming, small LNs (1.0 mm) may still be missed [5]. Therefore, the hot question of how to accomplish a complete LNs harvesting still remains, as most of the procedures proposed and applied so far were often disappointing [6,7]. This results in the increasing needing of a standardized and easily applicable operative protocol.…”
mentioning
confidence: 99%